Chemical composition and antioxidante activity of Tunisian Origanum glandulosum Desf. essential oil and volatile oil obtain by supercritical CO2 extraction - Mechergui, Kaouther (2015)
Dried flowers and leaves of Origanum glandulosum Desf. were submitted to hydrodistillation (HD) and supercritical fluid extraction with CO2 (SFE). The essential oils isolated by HD and volatile oils obtained by SFE were analysed by GC and GC/MS. Total phenolics content and antioxidant effectiveness were performed. The main components of the essential oils from Bargou and Nefza were: p-cymene (40.4% and 39%), thymol (38.7% and 34.4%) and γ- terpinene (12.3% and 19.2%), respectively. The major components obtain by SFE in the volatile oil, from Bargou and Nefza, were: p-cymene (32.3% and 36.2%), thymol (41% and 40%) and γ-terpinene (20.3% and 13.3%). Total phenolic content, expressed in gallic acid equivalent (GAE) g kg-1 dry weight, varied from 12 to 27 g kg-1 dw, and the ability to scavenge the DPPH radicals, expressed by IC50 ranged from 44 to143 mg L-1.